Thermal manipulation and GnRHa therapy applied to the reproduction of lambari-do-rabo-amarelo, Astyanax altiparanae females (Characiformes: Characidae)during the non-breeding season - Brambila-Souza, G. [UNESP]; Mylonas, C. C.; Mello, P. H. [UNESP]; Kuradomi, R. Y.; Batlouni, S. R. [UNESP]; Tolussi, C. E.; Moreira, R. G. (Elsevier, 2019)
Lambari-do-rabo-amarelo Astyanax altiparanae in the wild reproduce during spring and summer, but females undergo vitellogenesis throughout the year, including the non-spawning winter period when water temperatures are low. The present study investigated the physiological role of temperature modulation on the hypothalamus-pituitary-gonads axis of lambari during winter, as well as the effects of gonadotropin releasing hormone agonist (GnRHa)therapy. Captive females were exposed to two different temperatures (20 °C and 27 °C)and were injected weekly with GnRHa for 21 days during winter (Control, CTR; Low dose; LD and high dose of GnRHa, HD). At the end of the 21-days period gonadosomatic index (GSI), oocyte stage of development and theoretical fecundity were evaluated, together with plasma levels of 17β-estradiol (E2). Gene expression of the two pituitary gonadotropins follicle-stimulating hormone (fshβ)and luteinizing hormone (lhβ), as well as hepatic vitellogenin-A (vtgA)expression were also analyzed. At the end of the experimental period, females from the six different experimental conditions were induced to spawn using human chorionic gonadotropin (hCG). Spawning performance parameters and plasma levels of the maturation inducing steroid (MIS)were analyzed. Gene expression of fshβ did not change with temperature manipulation, but females exposed to 27 °C and supplemented with a HD of GnRHa exhibited an increased fshβ gene expression, associated with higher E2 levels. The higher water temperature alone was able to increase E2 levels. At both water temperatures GnRHa injections induced a decrease in E2 levels. GnRHa injected females had a lower vtgA gene expression levels at 20 °C. Even with differences in the gene expression of gonadotropins among the various temperature/GnRHa treatments, GSI and oocyte diameter did not change, but GnRHa enhanced the number of vitellogenic oocytes at 20 °C. The reproductive performance of lambari induced to spawn with hCG was better after the combined treatment with GnRHa and summer temperature.
Keywords: Estradiol; GnRHa; Gonadotropins; Induced spawning; Temperature; Vitellogenin